Modulating the electronic and optical properties of monolayer arsenene phases by organic molecular doping. (15th November 2017) - Singh, Deobrat; Gupta, Sanjeev K; Sonvane, Yogesh; Sahoo, Satyaprakash
Abstract: Recently, arsenene monolayer structure of the arsenic with two phases has displayed semiconducting behavior. We have systematically investigated the electronic and optical properties of single-layer arsenene with two types of functionalized organic molecules; an electrophilic molecule [tetracyanoquinodimethane (TCNQ)] and a nucleophilic molecule [tetrathiafulvalene (TTF)], as an electron acceptor and electron donor, respectively. The interfacial charge transfer between the arsenene monolayer and TCNQ/TTF molecules extensively reduces the band gap of arsenene and accordingly resulted in a p- or n-type semiconducting behavior, respectively. We have also performed the interfacial charge transfer from organic molecules to monolayer arsenene and vice versa. The interfacial surface molecular modification has established an efficient way to develop the light harvesting of arsenene in different polarization directions. Our theoretical investigation suggests that such n- and p-type arsenene semiconductors would broaden the applications in the field of nanoelectronic and optoelectronic devices such as photodiodes and it is also useful for constructing functional electronic systems.